Pengaruh Pemberdayaan dan Kinerja UMKM Terhadap Kesejahteraan Pelaku UMKM Perempuan Di Kabupaten Jember - Riniati Riniati; Susilo Ambarwati; Duwi Yunitasari (RELASI : JURNAL EKONOMI, 2023)
This study uses a quantitative research method with multiple regression analysis tools which aims to determine "The Effect of MSME Empowerment and Performance on the Welfare of MSME Actors in Jember Regency". Collecting data using a questionnaire with a purposive sampling technique. This research was conducted in Jember Regency using a sample of 97 female MSMEs in Jember Regency. The aim of the study was to determine the effect of empowerment and performance of SMEs on the welfare of female SMEs in Jember Regency. The results of the research on the empowerment variable (X1) partially have a positive and significant effect on the variable level of welfare of female MSME actors (Y) in Jember Regency. The MSME performance variable (X2) partially has a positive and significant effect on the variable level of welfare of female MSME actors (Y) in Jember Regency. The results of the study were to determine the effect of the empowerment variable (X1) and the MSME performance variable (X2) simultaneously (together) affecting the welfare level variable of female MSME actors (Y) in Jember Regency.